PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris pada Perusahaan BUMN yang Terdaftar pada Bursa Efek Indonesia Periode 2017-2021) - Ermalyani Margaret; Daljono Daljono (Diponegoro Journal of Accounting, 2023)
The purpose of this research is to examine the return on assets affected by good corporate governance the independent board of commissioners, board of directors, audit committee, managerial ownership, institutional ownership, and government ownership on Self-Owned Enterprise companies. Variables used in the examination are independent board of commissioners, board of directors, audit committee, managerial ownership, institutional ownership, government ownership also return on assets as the dependent variable.This research used manufacturing companies during 2017-2021 with a total sample size of 90 samples. Sampling is based on a purposive sampling method that follows certain criteria(s). Multiple linear regression analysis is the analysis method used in this research.The results of this study indicate that the board of directors, and institutional ownership have a positive significant effect on return on assets. Independent board of commissioners, audit committee, managerial ownership, and government ownership have no effect on return on assets.